Physical activity of men and women in the Liberec region regarding their daily activities - Aleš Suchomel; Dagmar Sigmundová (Palacký University Olomouc, 2011)
BACKGROUND: Physical activity is an important element in health enhancement and health promotion. We encounter physical activity while performing regular daily routines, at work, at home, or while exercising. The analysis of physical activity in the inhabitants of the region, with the regard to male and female roles provides information that can be used to support active lifestyle. AIMS: The main aim is to characterize physical activity of men and women in the Liberec region in the relation to their daily activities and to socio-environmental factors and to provide information that will serve in healthy and active lifestyle promotion. METHODS: The analysis included 448 men and 519 women aged 25-57. The research was carried out in 2005-2009 always in Spring and Fall. Physical activity was estimated using standardized ANEWS and IPAQ - the long version, questionnaires. RESULTS: The correlation analysis show significant associations between physical activity and socio-environmental variables. While assessing physical activity according to daily activities, men show significantly more physical activity at work than women (H = 30.12; p < 0.001; η2 = 0.031), and in transport (H = 7.1; p = 0.008; η2 = 0.007). On the other hand, women show more physical activity than men in the work in and around house (H = 22.4; p < 0.001; η2 = 0.023). CONCLUSIONS: Men are in total more physically active than women. To assess appropriatelly the level of physical activity, we have found the overall volume of physical activity to be the most useful information. On the other hand, to carry out effective health promotion, the information regarding the individual areas of physical activity need to be applied.